KEDUDUKAN MENTERI KEUANGAN DALAM KEPAILITAN PERUSAHAAN ASURANSI - Imbawani Atmadjaja, Djoko; Anwar, Anwar (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The research is aimed at investigating the exclusive position of the Minister of Finance as an applicant in an insurance companyâs bankruptcy. This given authority has brought up issues in relation to law particularly concerning principle obedience. Problems raised in this research are, first, has Article 2 (5) Act No. 37 Year 2004 fulfilled the justice principle especially in the context of the nationâs role? Second, the given authority is in accordance with the positions and functions of the finance minister as âthe governmentâ. The methodology used in this paper is normative research. The research findings are: first, the nationâs participation in organising and overseeing the insurance companyâs activities is fair. However, the chosen mechanism has actually ignored the law principles that have been agreed upon. The second finding, the position and the authority of the Minister of Finance as bankruptcy applicant has violated the positions and functions of a minister as it is already arranged in the Act of the Minister of State.